PELAKSANAAN UNDANG-UNDANG NOMOR 2 TAHUN 2012 TENTANG PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM DI KOTA SAMARINDA (STUDI KASUS PADA PEMBANGUNAN FLYOVER YANG MENGHUBUNGKAN JALAN AW. SJAHRANIE DAN JALAN JUANDA) - Panggih Nugroho; Parlindungan Pasaribu (Law Department, University of Widya Gama Mahakam Samarinda, 2016)
National development carried out in order to meet the mandate of the 1945 opening of the year to year increase. At the same time, the population has been continues to increase and it is relation with the development and results, it is increasing and the variety of all the needs of the population in Indonesia which is increasing with the level of prosperity is getting better it would require public facilities such as: network / transport facilities education, worship, sports facilities, communication facilities, public safety facilities and so forth. Construction of public facilities such as the above needs the land as the site. In terms of land supply is still widespread, the construction of public facilities had no problems, but that the problem in case is the area being used is soil that experienced land acquisition therefore whether infrastructure planning (flyover), which has been built in line with Law No. 2 the year 2012 on land Acquisition for Development for Public Interest.